Can realists reason with reasons? - Kietzmann, Christian (Philosophical Explorations, 2022)
I argue that realism about reasons is incompatible with the possibility of reasoning with reasons, because realists are committed to the claim that we are aware of reasons by way of ordinary beliefs, whereas a proper understanding of reasoning excludes that our awareness of reasons consists in beliefs. In the first three sections, I set forth five claims that realists standardly make, explain some assumptions I make concerning reasoning, and show why realism, so understood, cannot accommodate the truism that we reason with reasons. I then consider two proposals for how to avoid the problem.
CRIS-Team Scopus Importer:2022-03-18
Keywords: realism about reasons; reasoning; Reasons; taking condition